2008
DOI: 10.1590/s0036-46652008000600010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C virus infection in quilombo remnant communities in Central Brazil

Abstract: SUMMARYIn order to determine the prevalence of hepatitis C virus (HCV) infection in quilombo remnant communities in Central Brazil, 1,007 subjects were interviewed in all 12 communities existing in Mato Grosso do Sul State, Central Brazil. Blood samples were collected and sera were tested for anti-HCV by enzyme-linked immunosorbent assay. Positive samples were retested for confirmation using a line immunoassay and were also subjected to HCV RNA detection. The prevalence of HCV infection was 0.2%. This finding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The proportion of confirmed active infections among positive screening test results varies widely across studies and test types. The proportion of RNA-positive, active HCV infection cases ranged from 0% to 89.7% among positive antibody-based assays [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][45][46][47][48][51][52][53][54] and from 0% to 100% among antigen-based assays. 39,44,49,50 Only three studies conducted confirmatory polymerase chain reaction on samples that tested negative for HCV antibody or antigen.…”
Section: Box 1: Grading Of Recommendationsmentioning
confidence: 99%
“…The proportion of confirmed active infections among positive screening test results varies widely across studies and test types. The proportion of RNA-positive, active HCV infection cases ranged from 0% to 89.7% among positive antibody-based assays [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][45][46][47][48][51][52][53][54] and from 0% to 100% among antigen-based assays. 39,44,49,50 Only three studies conducted confirmatory polymerase chain reaction on samples that tested negative for HCV antibody or antigen.…”
Section: Box 1: Grading Of Recommendationsmentioning
confidence: 99%
“…Six studies were found that reported the prevalence of antibodies to hepatitis C virus (anti-HCV), with a range of zero to 5.7% (three from Brazil (64, 71, 86) and one each from Colombia (79), Mexico (31), and Paraguay (84)). Overall, the prevalence of hepatitis C was low, apart from the studies in Colombia (prevalence of 5.7% in Amazonas) and Mexico (prevalence of 4.2% among indigenous peoples from 12 urban areas).…”
Section: Resultsmentioning
confidence: 99%
“…In this area, there were indigenous, riverine and quilombo communities and recently almost one-third of the area was on fire. Reis et al [33] found 0.2% of anti-HCV prevalence among quilombo remnant communities in Midwest region of Brazil. The discrepancies in HCV prevalence and the impact of the fires that destroyed the environment reinforce the need for further epidemiological studies in this area.…”
Section: Discussionmentioning
confidence: 98%